Complex Identity: Genes to God - Love, Carolyn J. (Zygon, 2023)
Unraveling the complex notion of “self” and “other” necessitates a layered approach that explores biology, namely genetics; philosophy, namely event phenomenology; and culture, namely religion. This essay examines (1) the latest paradigm shift occurring in the genetic sciences due to the increased knowledge of epigenetic effects on gene expression and how our DNA functions in concert with the cellular apparatus, the body, and the environment; (2) the incorporation of relationality into a philosophical understanding of self; and (3) finally, what religion adds to this exploration of self. Thus, providing a glimpse at how these different approaches to identity help us understand the “self.”